Journal of Physiological Anthropology - Yasukouchi, Akira; Nakamura, Harunobu
Journal of Physiological Anthropology (JPA) is an open access, peer-reviewed journal that publishes research on the physiological functions of modern mankind, with an emphasis on the physical and bio-cultural effects on human adaptability to the current environment. The objective of JPA is to evaluate physiological adaptations to modern living environments, and to publish research from different scientific fields concerned with environmental impact on human life. Topic areas include, but are not limited to: environmental physiology bio-cultural environment living environment epigenetic adaptation development and growth age and sex differences nutrition and morphology physical fitness and health Journal of Physiological Anthropology is the official journal of the Japan Society of Physiological Anthropology.